A co-created nurse-driven catheterisation protocol can reduce bladder distension in acute hip fracture patients - results from a longitudinal observational study - Maria Frödin; Bengt Nellgård; Cecilia Rogmark; Brigid M. Gillespie; Ewa Wikström; Annette Erichsen Andersson (BMC, 2022)
Abstract Background Urinary retention is common in elderly patients undergoing acute hip fracture surgery. Avoiding overfilling the urinary bladder is important to avoid detrusor muscle damage and associated motility problems. The aim of this study was to analyse associations between the co-creation of a nurse-driven urinary catheterisation protocol and the incidence of bladder distension in patients undergoing hip fracture surgery. Methods This is a single-centre implementation intervention with a retrospective longitudinal observation design, using five measures points, spanning from June 2015 to March 2020. The intervention was theory driven and the participants, together with the facilitators and researcher, co-created a nurse-driven urinary catheterisation protocol. Data were retrieved from the hip fracture register. Uni- and multivariable logistic regressions were used for analyses of changes in bladder distension and urinary volume of ≥500 ml over the years. Results A total of 3078 patients were included over a five-year period. The implementation intervention was associated with a reduction in the proportion of patients with bladder distension of 31.5% (95% confidence interval 26.0-37.0), from year 1 to year 5. The multivariable analysis indicated a 39% yearly reduction in bladder distension, OR 0.61 (95% confidence interval 0.57-0.64, p <  0001). There was a reduction in the proportion of patients with a bladder volume of ≥500 ml of 42.8% (95% confidence interval 36.2-49.4), from year 1 to year 5. The multivariable analysis found a 41% yearly reduction in patients with a bladder volume of ≥500 ml, OR 0.59 (95% confidence interval 0.55-0.64, p <  0.0001). The intervention was associated with improved documentation of both catheter indications and removal plans. Conclusion The use of predefined catheter indications and a tighter bladder scanning schedule were associated with a reduction in the incidence of both bladder distension and urine volume ≥ 500 ml in hip fracture patients. Registered nurses can play an active role in the facilitation of timely and appropriate catheter treatment in patients with hip fractures. Trial registration Clinical Trial Registry ISRCTN 17022695 registered retrospectively on 23 December 2021, in the end of the study, after data collection.